Investigating the prevalence of high-risk behaviors among professional athletes - Asefi, A.; Ghanbari Barzian, A. (International Journal of High Risk Behaviors and Addiction, 2020)
The prevalence of high-risk behaviors among professional athletes as role models for their fans, especially adolescents and young people, is important to be considered. Thus, this study aimed to investigate the prevalence of HRBs in Iranian professional athletes. This cross-sectional study included 1,940 athletes that were active in eight popular sports from 12 cities of the country. Data were collected using stratified random sampling and a self-made high-risk behavior questionnaire. To analyze the data, descriptive statistical methods (tables, percentages, and total percentages) were used. The results showed the prevalence of doping among professional athletes was 3%. Besides, 0.3% of the professional athletes on average smoke daily, and 2% used shisha daily. Moreover, 2.5% of professional athletes drunk alcohol at least one time per month. Also, the prevalence of violence involvement among professional athletes was 4.1%, and the prevalence of illicit drug use was 0.3%. The research results showed all high-risk behaviors were prevalent to some degree among professional athletes.